(untitled) (Altre Modernità, 2021)
This paper discusses the discourse strategies used by former US President Donald Trump in the tweets in which he discusses the construction of the wall between the US and Mexico. Border walls play a very important role in today’s world in that they characterise discourses of exclusion and othering in geopolitical and cultural terms and indicate a revival of nationalism. By employing Proximization Theory, this paper shows how certain lexico-grammatical features of Trump’s tweets contribute to a nationalist and populist discourse which legitimises the construction of the wall on the basis of the threat coming from an “Other”.